2016
DOI: 10.1515/freq-2016-0065
|View full text |Cite
|
Sign up to set email alerts
|

Design of Compact Flower Shape Dual Notched-Band Monopole Antenna for Extended UWB Wireless Applications

Abstract: In this letter, a compact monopole antenna for ultra wideband (UWB) applications is proposed with small size of 18×20=360 mm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…It has already been reported that the utilization of band stop filter needs additional area to integrate which conclusively raises the complexity and cost of the design. Notch band characteristics have been found as the solution to avoid the interferences between UWB system and narrow band wireless system [23].…”
Section: Design Procedures Of Integrated Gsm and Uwb Antenna With Notcmentioning
confidence: 99%
“…It has already been reported that the utilization of band stop filter needs additional area to integrate which conclusively raises the complexity and cost of the design. Notch band characteristics have been found as the solution to avoid the interferences between UWB system and narrow band wireless system [23].…”
Section: Design Procedures Of Integrated Gsm and Uwb Antenna With Notcmentioning
confidence: 99%
“…12 Additionally, various other methods have been employed to introduce dual band-stop characteristics for rejecting the interference in the UWB antennas. [13][14][15][16][17][18][19][20] However, most of the designs have large footprints and average performances (in terms of peak gain, radiation pattern, etc. ).…”
Section: Introductionmentioning
confidence: 99%
“…The design of a MIMO radiation configuration faces challenges such as achieving a higher isolation between the interradiating elements. Two reported research papers [1,2] used fractal flower-shaped geometry where two different substrates were used in the design (FR4 and Rogers RTDuroid5880); both covered the UWB bandwidth for different specific applications when compared with the proposed work. The proposed work was designed for a MIMO configuration for encountering fading of the signals.…”
Section: Introductionmentioning
confidence: 99%